Numerical Analysis of the Combustion Dynamics of Passively Controlled Jets Issuing from Polygonal Nozzles - Łukasz Kuban; Jakub Stempka; Artur Tyliszczak (Energies, 2021)
In the present work, the combustion of vitiated hydrogen jets issuing from differently shaped nozzles is modelled using the LES method. We investigate the impact of nozzle cross-sectional geometries (circular, square, triangular, hexagonal and hexagram) and the jet Reynolds numbers (<semantics>Re=</semantics> 18,000, 20,000 and 23,600) on the flame lift-off height, its structure, the locations of the temperature maxima and species distributions. The triangular nozzle yields the highest mixing rate and therefore the fastest decay of axial velocity and the fastest growth of the average temperature along the flame axis. It was found that for the largest <semantics>Re</semantics>, the zone of intense mixing and the reaction zone occur in distinct regions, while for the lower <semantics>Re</semantics>, these regions combine into an indistinguishable zone. Finally, it is shown that the lift-off height of the flames and the mean temperature field are non-linearly correlated with <semantics>Re</semantics> and strongly dependent on the nozzle shape.